Seismic behavior of circular fly ash concrete columns reinforced with low-bond high-strength steel rebar. (October 2020) - Wang, J.H.; Sun, Y.P.; Takeuchi, T.; Koyama, T.
Highlights: Seismic behaviors of low cement high strength fly ash concrete column are studied. The residual drifts of specimen with LBHS steel rebars were experimentally studied. The thin bolted steel tubes were used to confine specimen column sections. The proposed OpenSees model could predict the seismic behaviors of specimens. Abstract: This paper proposes the use of concrete with a high water/cement ratio of 0.65, 455 kg/m 3 of mixed fly ash and low-bond high-strength (LBHS) rebar to develop resilient circular columns confined by bolted steel tubes. The test results indicated that the proposed bolted steel tube-confined fly ash concrete columns with LBHS rebar had great self-centering (SC) capacity and stable lateral load resistance until reaching a large drift value. Low bonds resulted in delayed yielding of the longitudinal rebar; therefore, the column had better deformability and durable SC capacity compared with a column with normal high-bond steel rebar. Furthermore, the anchorage tie plate at the contraflexure section of double curvature columns was necessary to prevent the steel rebar from slipping. Shortening the anchorage length of the longitudinal rebar within the beam-column joint had little influence on the seismic behavior of the test column. Bolted steel tubes could provide better safety for testing columns compared with that of welded steel tubes, especially at the large deformation stage. The proposed OpenSees model can evaluate the seismic behavior of the test columns with good agreement. The lateral behavior of the test columns can be reasonably predicted by using an equivalent stress block and calculation method considering steel bond slip. The literature indicated that the combination of LBHS rebar and fly ash concrete as well as bolted steel tubes is a good alternative for the development of SC RC columns.